2021
DOI: 10.7150/ijbs.57887
|View full text |Cite
|
Sign up to set email alerts
|

Promising diagnostic and therapeutic circRNAs for skeletal and chondral disorders

Abstract: Circular RNAs (circRNAs) belong to a highly conserved subtype of non-coding RNAs, produced by the back-splicing of specific regions of pre-mRNA. CircRNAs have wide-ranging effects on eukaryotic physiology and pathology by acting as transcription regulators, miRNA sponges, protein sponges, and templates for translation. Skeletal and chondral disorders are the leading causes of pain and disability, especially for elders, affecting hundreds of millions of people worldwide. Plenty of evidence have shown that circR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 125 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…Insufficient bone formation ability can lead to increased bone loss, thereby accelerating the progression of osteoporosis 1 . Many studies have confirmed that circRNAs play a critical role in the osteogenic differentiation of BMSCs 17,29 . Yin and Xue 30 found that hsa_circ_0006859 could promote the progression of osteoporosis by inhibiting miR‐642b‐5p/miR‐483‐3p and increasing the expression of EFNA2/DOCK3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insufficient bone formation ability can lead to increased bone loss, thereby accelerating the progression of osteoporosis 1 . Many studies have confirmed that circRNAs play a critical role in the osteogenic differentiation of BMSCs 17,29 . Yin and Xue 30 found that hsa_circ_0006859 could promote the progression of osteoporosis by inhibiting miR‐642b‐5p/miR‐483‐3p and increasing the expression of EFNA2/DOCK3.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, circular RNAs (circRNAs) have been considered key regulators for posttranscriptional level regulation due to their stable circular structure 15 . Recent studies have suggested that circRNAs play key regulatory roles in the osteogenic differentiation process of BMSCs 16,17 . However, the current lack of targeted vectors limits the translational application of circRNA in the treatment of PMOP.…”
Section: Introductionmentioning
confidence: 99%
“…24,33 MiRNAs, assisted by ago protein, can recognize the 3'UTR end of the mRNA and induce its degradation. 34,35 Studies have shown that many miRNAs are differentially expressed in OA articular cartilage and play key regulatory roles. 36,37 However, the expression profiles of miRNAs in DDH-OA have not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Several scholars have emphasized the substantial impact of circRNAs on the regulation of gene transcription by acting as miRNA sponges, boosting the expression of downstream mRNAs (31). A comprehensive interpretation of the role of epigenetically regulated miRNAs and the miRNA-mediated epigenetic modulation of genes is critical for understanding how aberrant miRNA expression might contribute to RA, and how this knowledge can be translated into diagnostic and therapeutic tool development (32).…”
Section: Discussionmentioning
confidence: 99%